Modification of Triclosan Scaffold in Search of Improved Inhibitors for Enoyl‐Acyl Carrier Protein (ACP) Reductase in Toxoplasma gondii. Issue 7 (14th June 2013) - Stec, Jozef; Fomovska, Alina; Afanador, Gustavo A.; Muench, Stephen P.; Zhou, Ying; Lai, Bo‐Shiun; El Bissati, Kamal; Hickman, Mark R.; Lee, Patty J.; Leed, Susan E.; Auschwitz, Jennifer M.; Sommervile, Caroline; et al.
Abstract Through our focused effort to discover new and effective agents against toxoplasmosis, a structure‐based drug design approach was used to develop a series of potent inhibitors of the enoyl‐acyl carrier protein (ACP) reductase (ENR) enzyme in Toxoplasma gondii (TgENR). Modifications to positions 5 and 4′ of the well‐known ENR inhibitor triclosan afforded a series of 29 new analogues. Among the resulting compounds, many showed high potency and improved physicochemical properties in comparison with the lead. The most potent compounds 16 a and 16 c have IC50 values of 250 nM against Toxoplasma gondii tachyzoites without apparent toxicity to the host cells. Their IC50 values against recombinant TgENR were found to be 43 and 26 nM, respectively. Additionally, 11 other analogues in this series had IC50 values ranging from 17 to 130 nM in the enzyme‐based assay. With respect to their excellent in vitro activity as well as improved drug‐like properties, the lead compounds 16 a and 16 c are deemed to be excellent starting points for the development of new medicines to effectively treat Toxoplasma gondii infections.